Lacosamide Lowers Valproate and Levetiracetam Levels - Tountopoulou, Maria; Weschke, Bernhard; Kaindl, Angela M. (Neuropediatrics, 2017)
Lacosamide (LCM) due to no known drug interaction and the absence of metabolic enzyme induction is a good candidate for an add-on medication, especially in combination with lamotrigine, levetiracetam (LEV), oxcarbazepine, topiramate, and valproic acid (VPA). Here we report for the first time, to our knowledge, that LCM can lower VPA and LEV serum levels. At present, there are no known explicable mechanisms of action of LCM, which lowers VPA and LEV. Here observed drug interaction of LCM is of clinical significance, which might be useful for other colleagues in the field.
Keywords: lacosamide; valproate; levetiracetam; interaction; drug-level